A Checklist of the Ornamental Vascular Flora of Sicily - Emilio Di Gristina; Giulio Barone; Gianniantonio Domina; Emilio Badalamenti; Maria Letizia Gargano; Giuseppe Venturella; Raimondo Pardi (Plants)
Based on literature data and new field investigations, a checklist of the ornamental vascular flora of Sicily is presented. Trees, shrubs, herbaceous, and succulent plants growing in street trees, parks, private gardens, and historic villas of Sicily are included in the checklist. For each taxon, information on growth forms, geographical and biome origin, resident time, and status (native/alien) in Italy is provided. A total of 928 taxa (including 823 species s. str., 33 cultivars, 31 hybrids, 24 varieties, 9 subspecies, and 8 forms), belonging to 486 genera included in 138 families, were recorded. Fabaceae, Rosaceae, Asteraceae, Cactaceae, Asparagaceae, Arecaceae, and Malvaceae are the richest families in taxa. Phanerophytes are the prevalent growth form, and the main part of such flora consists of Asiatic and American taxa. Taxa from subtropical and tropical biomes showed a prevalent presence; this is a peculiarity which characterizes the Sicilian ornamental flora. Delonix regia emerges as a peculiar case, representing the only documented cases of open-air cultivation in both Sicily and the entire country. A significant percentage of taxa (41%) is included in the list of alien vascular flora of Italy, showing a strong predominance of casual and naturalized neophytes alien species.